Blended learning: Investigating the influence of engagement in multiple learning delivery modes on students' performance. Issue 7 (October 2018) - Baragash, Reem Sualiman; Al-Samarraie, Hosam
Highlights: The effects of students' engagement in three learning delivery modes on their online learning performance was examined. The mediation between students' learning experience and their learning performance was investigated. Certain modes of delivery can influence students' learning experience, thus influencing their performance. Abstract: The current reliance on different modes for delivering learning materials and establishing connections among peers can be significantly attributed to the teaching and learning practices in higher education. Here, the possible effects of students' engagement in multiple learning delivery modes on their academic performance were examined. This study specifically examined the effects of students' engagement in three learning delivery modes—face-to-face (F2F) learning, learning management system (LMS)-based learning, and web-based learning (WBL)—on their learning experience and performance. A total of 196 questionnaires were administrated to university students (104 male; 92 female) to assess their perception of the three modes. Log records were also obtained to investigate the mediation effect of students' learning experience in LMS-based learning (by access, time spent, tools usage) and WBL (by web tools usage and self-learning time) on their learning performance. Results of a partial least-squares structural equation modeling (PLS-SEM) analysis revealed that students' engagement in the F2F mode had a significant positive effect on their engagement in the LMS and WBL modes. Moreover, LMS time and tools usage had a positive influence on students' learning performance in the blended learning environment. Thus, the study results evince the effectiveness of multiple learning delivery modes on the learning development of students in higher education.